COMPARATIVE STUDY OF GENERATIVE AI TOOLS IN VISUAL COMMUNICATION DESIGN EDUCATION: CREATIVITY AND USABILITY - Yana Erlyana; M Garry Saputra (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2026)
The integration of generative artificial intelligence (AI) into visual communication design education presents opportunities to enhance creativity and usability in learning. This study compares the effectiveness of three generative AI tools (MidJourney, DALL·E, and Adobe Firefly) in supporting students’ creative outcomes and perceived usability, while also examining their broader pedagogical role in design education. A quasi-experimental design was conducted with 30 undergraduate students who each produced two poster designs: one manually and one with AI assistance. Creativity was evaluated using the Consensual Assessment Technique (CAT) by expert judges, and usability was measured using the System Usability Scale (SUS). Results showed that AI-assisted designs achieved significantly higher creativity scores (M = 4.3 vs. 3.2, p < 0.05) and usability ratings (range M = 74–82) compared to manual designs, with MidJourney rated highest in creativity and Adobe Firefly in usability. These findings provide empirical evidence that generative AI can act as a catalyst for creativity and usability in design education, offering theoretical insights into human–AI co-creation and practical implications for curriculum integration. Limitations include the small sample size and the study’s focus on a single academic program, which may affect generalizability.